129k views
4 votes
18) y-(4- x - y + 2); use x = 3, and y = 2

2 Answers

1 vote

Answer:

1

Explanation:

y-(4-x-y+2)

now substitute the values

= 2-(4-3-2+2)

= 2-(6-5)

= 2- 1

= 1

User Jonan
by
5.0k points
7 votes

Answer:

Do the problem, but change y to 2 and x into 3

2-(4-3-2+2)

2-(1-2+2)

2-(1)

2-1=1

1 is the answer

Hope this helps

Explanation:

User Ukjent
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.